Communicative Values of Harmonious Communication (according to Russian and Chinese Phraseology) - W. Li (Научный диалог, 2017)
The article is devoted to the linguocultural analysis of communicative values of harmonious communication presented in Russian phraseology and seen against the background of the Chinese communication culture. The relevance of the study is determined by increased conflictness in modern communications and the need to reflect national cultural traditions of communication. The material for the study are collocations with the meaning of “communicative behaviour,” extracted by the method of continuous sampling from the Russian and Chinese phraseological dictionaries (over 300 units). Phraseological units contain specific requirements prescribing the necessary communicative behaviour of addresser and addressee, who are equally responsible for the development and successful completion of the communicative interaction. The author identified the linguistic means characterizing a harmonious communication (evaluative adjectives, comparisons, direct prescriptions). Based on linguoculturological interpretation of phraseology, the author defines prescriptive standards and values for harmonious communication in Russian culture - politeness, sincerity, absence of conflict. The results of comparative analysis of the maxims of benevolence, sincerity and tolerance are presented. Similarities of the communicative requirements of the Russian and Chinese cultures are shown. The author dwells on the specific qualities of sincerity and truthfulness, determined by the Russian mentality. Special attention is paid to restraining communicative actions hindering the communication process, which are registered in the national phraseology. It is proved that a harmonious communicative behaviour is governed by the rules of speech etiquette, based on the norms of morality and national cultural traditions.